Peran Kecerdasan Linguistik terhadap Keterampilan Menyimak Podcast Edukasi Siswa MA di Kabupaten Polewali Mandar - Rafika Saleh; Salam Salam; Asia Asia (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Listening skills constitute a fundamental component of language learning; however, their development continues to face various challenges, particularly within digital-media-based instruction. One internal factor presumed to play a significant role in listening proficiency is linguistic intelligence. This study aims to describe the role of linguistic intelligence in shaping the educational podcast listening skills of eleventh-grade Madrasah Aliyah (MA) students in Polewali Mandar Regency. Employing a qualitative descriptive approach, the study involved 103 students as research participants. Data were collected through a linguistic intelligence questionnaire, an educational podcast listening skills test, preliminary interviews, and documentation. The questionnaire was developed based on Gardner’s indicators of linguistic intelligence, while the listening test was administered after students listened to the Insantama School Podcast episode entitled “Pemuda Mengubah Peradaban.” Data analysis followed the interactive model proposed by Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings indicate that linguistic intelligence generally enhances students’ educational podcast listening skills, particularly in comprehending content, identifying details, selecting appropriate diction, and interpreting message meaning. Specifically, students’ linguistic intelligence was classified at a moderate-to-good level and contributed positively to listening performance, especially in expressing ideas, understanding texts, and using language creatively. Therefore, linguistic intelligence plays a crucial role in supporting the development of educational podcast listening skills among MA students in Polewali Mandar Regency.